2018
DOI: 10.1080/20002297.2018.1495975
|View full text |Cite
|
Sign up to set email alerts
|

In situ substrate-formed biofilms using IDODS mimic supragingival tooth-formed biofilms

Abstract: This study aimed to compare the bacterial viability and diversity of a substrate-formed biofilm (SF-biofilm) in situ to a supragingival tooth-formed biofilm (TF-biofilm) in the same group of individuals. The impact of the device/disc position and toothbrushing during the formation of SF-biofilm was also assessed. Two tests were run. In test 1, 15 volunteers wore two hemi-splints carrying six discs of human enamel, glass, and hydroxyapatite for 2 days, and were instructed to not perform any oral hygiene measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The device consists of a soft flexible inner splint and a more rigid outer splint carrying the glass substrate in between the two splints. Most workers placed the appliance in one jaw only, either the upper jaw [5,13,14,[21][22][23][24][25][30][31][32][33] or the lower jaw [19,27,29,[30][31][32][33][34]37]. However, Auschill et al [20], Langfeldt et al [26] and Tomas et al [34] placed the appliance in both jaws to investigate the differential characteristics of the biofilm growing in both the upper and lower jaws.…”
Section: The Appliance and Substrates Used To Collect Biofilmmentioning
confidence: 99%
See 4 more Smart Citations
“…The device consists of a soft flexible inner splint and a more rigid outer splint carrying the glass substrate in between the two splints. Most workers placed the appliance in one jaw only, either the upper jaw [5,13,14,[21][22][23][24][25][30][31][32][33] or the lower jaw [19,27,29,[30][31][32][33][34]37]. However, Auschill et al [20], Langfeldt et al [26] and Tomas et al [34] placed the appliance in both jaws to investigate the differential characteristics of the biofilm growing in both the upper and lower jaws.…”
Section: The Appliance and Substrates Used To Collect Biofilmmentioning
confidence: 99%
“…Different solid substrates with varying properties have also been used in these studies for instance human enamel in the Leeds in situ device [5,13], human enamel-dentine slab [30], bovine enamel/dentine [19,[22][23][24]31], polished glass [14,20,21,25,29,[34][35][36][37][38][39][40], hydroxyapatite discs [27,[32][33][34], or membrane filters [26]. Although the roughness of the surface of the substrate and its free energy are considered important factors for in vivo growth of the biofilm, Auschill et al [20] and Netuschill et al [41] found no major differences in the thickness of 48-h biofilm grown on enamel or glass discs.…”
Section: The Appliance and Substrates Used To Collect Biofilmmentioning
confidence: 99%
See 3 more Smart Citations